NETFLIX’S POTENTIAL AS AN ADDED TOOL IN LEARNING ENGLISH SPEAKING SKILLS: A SURVEY STUDY OF ESL SPEAKERS IN SUNWAY UNIVERSITY, MALAYSIA - Farah Shalin Binti Amanah; Sarah Binti Abdul Zaki; Fatin Irwani Binti Muhamad HairulZaki; Nor Haziqah Binti Ahmad (Journal of Islamic, Social, Economics and Development, 2023)
The study aims to investigate Netflix's potential as an added tool in learning English speaking skills among non-native English speakers specifically international students at Sunway University, Subang Jaya, Malaysia. A qualitative research design with a survey study technique was utilised for this study. It is designed to examine (1) Netflix's contribution in improving English speaking abilities and fluency among non-native English speaking international students at Sunway University, Subang Jaya, Malaysia, (2) to investigate the impact of Netflix towards non-native English speaking international students from Sunway University, Subang Jaya, Malaysia to their motivation in learning English speaking skills, and (3) to find out a movie or show genres in Netflix that are effective in learning spoken English for non-native English speaking international students in Sunway University, Subang Jaya, Malaysia. The participants of this study consist of six participants who are non-native English speaking international students currently studying at Sunway University, Subang Jaya, Malaysia. The research was conducted with one instrument, which is an interview. The findings indicated that Netflix has the potential to be an added tool in learning English speaking skills for non-native English speakers. The study proved that Netflix can positively improve English speaking abilities and fluency, enhance the English learners' motivation in speaking the language, as well as the ability to provide some suitable genres of programs that can contribute towards improving English speaking abilities. This study would help English learners or non-native English speakers who specifically want to improve their English speaking skills to have an insight into Netflix's potential as a new language learning material.